Faktor Kesalahan Pengelolaan Persediaan Medis Terhadap Perhitungan Beban Persediaan Medis Puskesmas X - Muhammad Arthur Agstrino; Tituk Diah Widajantie (Jurnal Masyarakat Mengabdi Nusantara, 2023)
Inventory management at Puskesmas BLUD "X" is a mandate from Peraturan Pemerintah Nomor 27 Tahun 2014 and Peraturan Pemerintah Nomor 28 Tahun 2020 concerning BMN / BMD Management and its amendments. Peraturan Menteri Dalam Negeri Nomor 19 tahun 2016 concerning Guidelines for Regional Property Management (BMD). Moreover, Peraturan Menteri Dalam Negeri Nomor 47 Tahun 2021 concerning procedures for implementing BMD bookkeeping, inventory, and reporting, Kebijakan Akuntansi Pemerintah Daerah on inventory, Standar Akuntansi Pemerintah on inventory. In this study, it was found that inventory management at the Puskemas BLUD "X" was still inadequate and not in accordance with applicable regulations. The purpose of this study was to determine the error factor in the management of medical supplies Puskesmas BLUD "X" which is not in accordance with applicable regulations. The methods used in this study are comparative descriptive qualitative with the type of case study, and data collection techniques through triangulation (interviews, observations, and documentation). The result of this study is that inventory management at the Puskesmas BLUD "X" is still inadequate due to several factors, namely the non-functioning of operational standards in terms of recording, the quality of the internal control system is still weak, and the weak use of the SIM Persediaan Puskesmas, where these factors affect the results of the calculation of medical inventory expenses presented in the financial statements.